Hospitalisation with injection‐related infections: Validation of diagnostic codes to monitor admission trends at a tertiary care hospital in Melbourne, Australia. (11th April 2022) - Curtis, Stephanie J.; Langham, Freya J.; Tang, Mei Jie; Vujovic, Olga; Doyle, Joseph S.; Lau, Colleen L.; Stewardson, Andrew J.
Abstract: Introduction: Injection‐related infections (IRI) cause morbidity and mortality in people who inject drugs. Hospital administrative datasets can be used to describe hospitalisation trends, but there are no validated algorithms to identify injecting drug use and IRIs. We aimed to validate International Classification of Diseases (ICD) codes to identify admissions with IRIs and use these codes to describe IRIs within our hospital. Methods: We developed a candidate set of ICD codes to identify current injecting drug use and IRI and extracted admissions satisfying both criteria. We then used manual chart review data from 1 January 2017 to 30 April 2019 to evaluate the performance of these codes and refine our algorithm by selecting codes with a high‐positive predictive value (PPV). We used the refined algorithm to describe trends and outcomes of people who inject drugs with an IRI at Alfred Hospital, Melbourne from 2008 to 2020. Results: Current injecting drug use was best predicted by opioid‐related disorders (F11), 80% (95% confidence interval [CI] 74–85%), and other stimulant‐related disorders (F15), 82% (95% CI 70–90%). All PPVs were ≥67% to identify specific IRIs, and ≥84% for identifying any IRI. Using these codes over 12 years, IRIs increased from 138 to 249 per 100 000 admissions, and skin and soft tissues infections (SSTI) were the most common (797/1751, 46%). Discussion and Conclusion: Validated ICD‐based algorithms can inform passive surveillance systems. Strategies to reduce hospitalisation with IRIs should be supported by early intervention and prevention, particularly for SSTIs which may represent delayed access to care.